Effect of Bullying on the Risk of Anxiety and Social Interaction Disorder among Senior High School in Yogyakarta - Hainas Sani Privetera; RB Soemanto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2020)
Background: Bullying is a widespread phenomenon among young people and is used to describe interpersonal relationships characterized by an imbalance of power. The Indonesian Child Protection Commission noted that there were 161 cases of bullying in 2018. Adolescents who are involved in bullying experience risks such as psychiatric symptoms, alcohol and drug abuse and even suicide. This study aims to analyze the effects of bullying on self-concept and social disorders in high school students in Sleman Yogyakarta.Subjects and Method: This study used a cross sectional study design. This study was conducted in Sleman Regency in August 2019. The sample was taken by using stratified random sampling with a total of 200 senior high school students. The independent variables include parental education, social environment, anxiety level, self-concept, and social interaction disorders. The dependent variable was bullying behavior. Data were collected using a questionnaire. Data were analyzed by using multilevel multiple logistic regression with stata 13.Results: Low family education (b= 3.11; 95% CI= 0.83 to 3.67; p= 0.002), social environment in the city (b=3.15; 95% CI= 0.71 to 3.09; p= 0.002), have social media (b=4.13; 95% CI= 1.46 to 3.83; p= 0.000), have a level of anxiety (b= 2.92; 95% CI= 0.62 to 3.17; p= 0.005), negative self-concept (b=2.83; 95% CI= 0.62 to 3.40; p= 0.005), social interaction disorder (b= 3.23; 95% CI= 0.87 to 3.55; p= 0.001) increased the likelihood of experiencing bullying in adolescents. Variations at the school level indicated that there was a contextual influence on bullying behavior (ICC= 13.18%).Conclusion: There is a statistically significant influence of parental education, social environment, social media, anxiety levels, self-concept, and social interaction disorders on bullying behavior in adolescents. Variations at the level of school show that there is a contextual influence on bullying behavior in adolescents.Keywords: bullying, adolescents, multilevel analysisCorrespondence: Hainas Sani Privetera. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: sariprivitera@gmail.com. Mobile: +6282328848001.Journal of Health Promotion and Behavior (2020), 05(04): 306-316https://doi.org/10.26911/thejhpb.2020.05.04.08.